Renewable Energy – a New Direction in the European Energy Market Evolution - Delia Vasilica Rotaru (CES Working Papers, 2014)
Nowadays, renewable energy represents one of the most debated subjects on the global energy market. The global warming and the constraints of the traditional energy resources led to the reorientation of countries in exploiting alternative resources. This paper offers a presentation of the main sources of renewable energy present worldwide and the way these can be exploited. Also, the paper analyses the main policies and taxes put in practice by the EU members to support the development of renewable sector, given the 2012/27/EU Directive that establishes several targets that need to be achieved on the market by 2020. Finally, the evolution of the main renewable energy market indicators is being reviewed, showing that considerable progress has been made in the last few years.
Keywords: Q01; Q42; Q54; 330; renewable energy; energy efficiency; CO2 emissions Romania